European modernity : a global approach - Stråth, Bo (Europe's legacy in the modern world, 2017)
"It is often taken for granted that modernity emerged in Europe and diffused from there across the world. This book questions that assumption and re-examines the question of European modernity in the light of world history. Bo Stråth and Peter Wagner re-position Europe in the global context of the 19th and 20th centuries. They show that Europe is less modern than has been assumed, and modernity less European and thus decentre Europe in a way that makes room for a wider historical perspective. Adopting a thematic structure, the authors reconceive the idea of European modernity in relation to key topics such as democracy, capitalism and market society, individual autonomy, religion and politics. European Modernity is an important addition to the literature that will be of interest to all students and scholars of modern European history"--Provided by publisher